Sikap terhadap sains dan sikap saintifik di kalangan pelajar sains - Kamisah Osman, -; Zanaton Haji Iksan, -; Lilia Halim, - (penerbit ukm, 2007)
Attitude research might have something to offer in providing possible explanation for the persisting problem of the alienation of students from science. This study aims to determine the level of students’ attitudes towards science and of their scientific attitudes and the diffrentiaton according to gender, ethnicity and educational levels. It also aims to investigate the relationship between students’ attitudes towards science and scientific attitudes. A total of 493 Forms 2, 4 and matriculation students responded to questionnaires on attitudes towards science and scientific attitudes. The questionnaire on attitudes towards science consists of 48 items and multi-dimensional in nature (Perception towards science teachers, anxiety towards science, value of science in society, self concept in science, enjoyment in science and motivation in science). The questionnaire on scientific attitudes consists of 23 items measuring critical mindedness, suspended judgment, respect for evidence, honesty,objectivity and willingness to change opinions. The findings indicated that students’ self concept in science and motivation in science require further attention compared to the other dimensions of attitudes toward science. Both dimensions are predictors to students’ involvement in science at higher educational level and in the society in the future. The level of students’ scientific attitudes between gender, ethnicity and across educational levels is found to be low. This finding has an implication on the way science should be taught and learned in that it should be more inquiry and ‘hands-on’ based. Lastly, there axist weak relationship between students’ attitudes toward science and scientific attitudes among the Form 2 and matriculation students.